Parental Chronic Illness Impact on Children: Family Status, Aspects of Relationships and Patients’ Illness Perceptions in Association with the Total Score of CBCL and SCL90 - Arkouli, Theodora; Canellopoulos, Vassiliki (International Journal of Psychology, 2025)
Purpose: The goal of this study is to define in which ways certain conditions of parental chronic illness affect children’s mental health. Precisely, we expect to find answers in a series of research questions about the relation between demographic characteristics of chronic patients, family status, family relationships, role of illness as perceived subjectively by parents and the Scores in the Child Behavior Checklist (CBCL) and Symptom Checklist 90 Revised (SCL-90-R). Current study’s aim is to define whether and how family conditions mediate children’s psychological impact due to parental chronic illness. Methodology: The study adopted a qualitative descriptive research design. To collect data, we administered questionnaires to a Greek non-probability purposeful sample of chronically ill parents (N = 182) having children up to 18-years-old. The participants were recruited via on line communities. All the scales have good or excellent reliability (Cronbach’s alpha values greater than 0.8). All ethical requirements and General Data Protection Regulations (GDPR) were followed. Ethics committee of National and Kapodistrian University of Athens approval number is: 674/22/05/2025. The IBM SPSS Statistics 24 software was used for the analysis and the significance level of the tests was set at 0.05. Tables were also used to present the data. Findings: Main findings of the study as revealed from the analysis are the following: patients’ relationship status (married / in relationship vs divorced or single) and support received by their partner are significantly related with the total CBCL scores. Among married patients, 6.2% of their children are in borderline or clinical range, whereas the corresponding percentage for those that are divorced, or single parents is 18.9% (p=0.023). The percentage of the children who are in borderline or clinical range for emotional or behavioral problems is significantly higher among the patients who receive a little or none support by their partner (20.5%) compared with children of patients that receive a lot or moderate support (6.1%, p=0.007). Patients that declare that the role of illness in their life is heavy score on average significantly higher in the total scale of SCL90 than those that declare that the role of illness is moderate or minimum (1.05 ± 0.75 vs. 0.66 ± 0.48, p=0.001). Patients who declare that the illness has affected their child also score on average significantly higher in the total scale of SCL90 than those that don’t believe or are not sure that illness has affected their child (1.07 ± 0.70 vs. 0.78 ± 0.69, p=0.001). Patients whose child’s reaction about the illness is acceptance score significantly lower in the total scale of SCL90 than those that their child’s reaction was fear / anxiety / sadness (0.74 ± 0.61 vs. 1.01 ± 0.62, p=0.005). Unique Contribution to Theory, Practice and Policy: The present study suggests that regardless of the kind of chronic illness or severity spectrum, the patient’s subjective positivity towards the illness, the strong bond between partners and the patient’s feeling of support, seem to be fundamental mediators of parent/patient feeling of coping and children’s wellbeing. The family’s climate, the couple’s positive relationship and the availability of the healthy parent or even the ill one to relate to, seem to reduce negative outcomes of illness and children’s psychological burden. Given the strong association between children’s wellbeing and family relationships, we can assume the importance to include the entire family in chronic illness care policies and measures. Identifying protective factors in the context of interaction between parental chronic illness and mental distress in children could guide mental health promotion strategics to enhance all family members well-being.